2013
DOI: 10.1007/s10517-013-2016-5
|View full text |Cite
|
Sign up to set email alerts
|

Content of Vitamins B1 and B2 in Germinating Grain

Abstract: The content of vitamin B1 in wheat and rye grain remained at a constant level and that of vitamin B2 gradually increased during germination over 5 days at 20°C (in the dark). Significant difference was observed for rye within 1 day and for wheat in 2 days. By day 5, the content of vitamin B2 in both crops increased by 2.7-2.9 times above the baseline value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Germination did not significantly modify thiamin content, but increased 50% the levels of riboflavin in sprouted oat powder (Table 1). These results are in agreement with those previously found in germinated wheat and rye, which showed higher levels of riboflavin than non-germinated grains while thiamine content remained almost constant (Rahmatullina, Doronin, Vrzhesinskaya, & Kodentsova, 2013). Rico et al (2020), however, observed a strong increase of both vitamins in flour obtained from barley after germination at 12-20 ºC for 0.8-6.19 days.…”
Section: Resultssupporting
confidence: 92%
“…Germination did not significantly modify thiamin content, but increased 50% the levels of riboflavin in sprouted oat powder (Table 1). These results are in agreement with those previously found in germinated wheat and rye, which showed higher levels of riboflavin than non-germinated grains while thiamine content remained almost constant (Rahmatullina, Doronin, Vrzhesinskaya, & Kodentsova, 2013). Rico et al (2020), however, observed a strong increase of both vitamins in flour obtained from barley after germination at 12-20 ºC for 0.8-6.19 days.…”
Section: Resultssupporting
confidence: 92%
“…Riboflavin content in moringa seeds was higher than values previously reported in other moringa varieties [28]. The content of riboflavin in moringa did not change or even increased during germination, and the highest values were observed at 28 • C and 24 h. It has been found that the content of riboflavin increased gradually throughout the germination period up to the fifth day in rapeseeds [32] and wheat seeds [33]. However, our results indicate that riboflavin levels in moringa sprouts decreased with increasing germination time.…”
Section: Effect Of Germination Conditions On Vitamin B 1 and B 2 Contmentioning
confidence: 50%
“…In particular, for the production of a large number of food products, grains of various crops that are at rest are used. At the same time, it is known that when grain germinates, the enzymes contained in it are activated, leading to a change in its chemical composition and nutritional value [1,11,13]. Various cereals are used as grain raw materials in the production of food products from germinated grain.…”
Section: Introductionmentioning
confidence: 99%